Pembangunan kemahiran kepimpinan pelajar melalui latihan lakon teater - Kalinggalan, Mazrona; Amat, Asmiaty; Husin, Fazilah (Universiti Malaysia Sabah (UMS), 2024)
This research investigated the impact of the actor's training preparation approach on the development of leadership skills among students. It was administered for fourteen weeks to 35 respondents who were enrolled in institutions of higher education. The methodology of the investigation incorporates qualitative and quantitative approaches. The data for this study were gathered via two distinct approaches: focus group interviews and questionnaire responses obtained both prior to and subsequent to the module's implementation. Coding techniques were utilised to analyse the results of the focus group interviews in accordance with the sub-attributes delineated in the “Modul Pembangunan Kemahiran Insaniah Pelajar Institusi Pengajian Tinggi”. The questionnaire data were analysed utilising the T-test in the Statistical Package for the Social Sciences (SPSS) software in order to compare the responses before and after the actor training was implemented. The findings derived from the evaluation of both approaches indicate that the participants' leadership capabilities improve significantly subsequent to completing actor preparation training.